Method for increasing the accuracy of quantitative determination of iron by LIBS - Fomin, V.N.; Aldabergenova, S.K.; Rustembekov, K.T.; Dik, A.V.; Kim, Yu.Yu.; Rozhkovoy, I.Ye. (Ye.A.Buketov Karaganda State University Publ., 2018)
The problems of improving the chemometric characteristics of spectral methods of analysis are being intensively studied throughout the world. These problems are especially significant in the field of laser atomic emission spectrometry. In the article, it is proposed to use sample homogenization by fusion with sodium tetraborate. The example of iron in a mixture of oxides consisting of Fe2O3, PbO, CuO, CdO and ZnO has shown that fusion provides advantages over pressing, consisting in increasing the intensity of the spectral lines and increasing the accuracy of the concentration / intensity correlation, as well as an increase in the total number of spectral lines, which can be calibrated satisfactorily. Using the probabilistic-deterministic planning of the experiment and using the composite factor, it is shown that fusion substantially weakens the interrelation of the intensity of the spectral line with the instrument settings, which simplifies the choice of the spectrum registration regime. The observed regularities are explained by the high homogeneity of the vitreous samples, the more complete evaporation of the sample in the laser spark and the absence of interference in the form of a neat atomized sample, an increase in the density (and hence the concentration) of the sample. In the course of the experiments it was additionally established that for melting specimens, it was necessary to use the crucibles from alumina with caution. They dissolve rather quickly in the melt of tetraborate. Nickel crucibles can be used only if nickel is not among the elements that are determined in the sample. Based on the results of the study, there was made a conclusion about the need study of the proposed methodology and its extension to other elements of the periodic system for further.
ЛАЭС көмегімен темірді сандық анықтаудың дəлдігін арттыру əдісі
Метод повышения точности количественного определения железа с помощью ЛАЭС
Keywords: iron; sodium tetraborate; regression analysis; laser inducted breakdown spectroscopy; borate glasses; borate pressing; stochastic-determinated design of experiments; chemometrics; Fe2O3; PbO; CuO; CdO; ZnO